Implementation of green, lean and six sigma operations for sustainable manufacturing. A review - Khalid Nagadi (International Journal of Production Management and Engineering, 2022)
With ever increasing environmental concerns and global warming, green manufacturing has gained momentum to make the manufacturing processes sustainable and efficient. This review aims to analyse the models to integrate three different management systems that are green, six sigma and lean for the sustainability of various manufacturing processes. Research gaps for such integration are identified through a literature review of various studies. The importance of the concepts of eco-friendly and sustainability in business operations and practices is growing rapidly as a result of public pressure, government regulations and social responsibilities. The first step is the identification of sustainability assessment for the current industrial processes and then to make them eco-friendly and more efficient through different green, six sigma and lean tools available. The methodology presented in this review will not only help in sustainability but also is helpful in the integration of various models for the improvement of the processes. Green Lean Six Sigma (GLS) is an approach known to minimize emissions and carbon footprints while improving process efficiency. GLS includes green, six sigma and lean methodologies for high performance, sustainability, social development, economic progress and environmental protection. The successful integration of this GLS approach is dependent on different theoretical indicators and the model is developed based on DMAIC. Various tools, enablers and integration methods are employed for the GLS approach.